Transverse vibration of orthotropic rectangular plates under moving bodies - Khang, Nguyen Van; Phuong, Nguyen Minh (Vietnam Journal of Mechanics, 2009)
The use of orthotropic plates is common in all the fields of structural engineering: civil, traffic, aerospace and naval. In this paper the transverse vibration of orthotropic rectangular plates under moving bodies is investigated. The method of substructures is used to derive transverse vibration equations of an orthotropic rectangular plate under the action of moving bodies. For the calculation of dynamic response of orthotropic rectangular plate we use Ritz method and numerical integration method